How Ibrahim came to know Allah? - Khan, Saniyasnain (Goodword Books: New Delhi, 2010)
The book narrates the journey of Prophet Ibrahim (Abraham) in discovering the one true God, Allah. Growing up in a society that worshipped idols, Ibrahim (AS) questioned the logic of idol worship. He observed the natural world, noticing that the star, moon, and sun all disappeared, leading him to conclude that they could not be gods. This reflection guided him to recognize that the Creator of the heavens and the earth must be eternal and beyond the physical world. His quest for truth led him to submit to Allah, marking the beginning of his prophethood.